KINERJA KEUANGAN INDUSTRI CITRA LESTARI PRODUCTION KOTA PALU - Ani, Apriani; Yantu, Marwan; Howara, Davina (AGROTEKBIS, 2013)
Horticultural and food crops are the vital sub sectors of agriculture that strongly support economic development of Central Sulawesi, however there are several constraints.  Farmers have lack of capital, lack of knowledge, and less of Agro-industrial activities. Palu city is one of well known producer of horticultural crops in Indonesia. In this city there are several industries producing snacks from horticultural products,  as added value to horticulture products.  Citra Lestari Production is a home industry in Palu, and whether this home industry could become a limited liability company (CV) will be studied, from its ability to purchase raw materials and good financial performance. Thus this study aimed to analyze whether Citra Lestari could become a limited liability company (CV) by analyzing its liquidity, solvency, and rate of return (profitability). Location and respondent of this study were determined deliberately. The results indicated that the level of liquidity of this company rose from 1.23 in 2010 to 1.36 % in 2011. Solvency level in 2010 was 8.43 and increased in 2011 to 8.53 %. The rates of return decreased from 86.59 in 2010 to 42.39% in year 2011. Based on these three aspects of financial ratios namely liquidity, and solvency, profitability/rate of return,  it is concluded that Citra Lestari Production could become a limited liability company (CV). This company has enough